2021
DOI: 10.1002/alr.22787
|View full text |Cite
|
Sign up to set email alerts
|

Targetable pathogenic mechanisms in nasal polyposis

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) represents a challenging disease entity with significant rates of recurrence following appropriate medical and surgical therapy. Recent approval of targeted biologics in CRSwNP compels deeper understanding of underlying disease pathophysiology. Both of the approved biologics for CRSwNP modulate the type 2 inflammatory pathway, and the majority of drugs in the clinical trials pathway are similarly targeted. However, there remain multiple other pathogenic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 171 publications
0
20
0
Order By: Relevance
“…Many of these drugs were first developed for other type 2 inflammatory diseases (ie, asthma and atopic dermatitis), providing important evidence for safety as well as efficacy against mechanistically similar diseases. Published ongoing trials in CRS include trials of mAbs targeting cytokines or their receptors (lebrikizumab [anti-IL-13], reslizumab [anti-IL-5], benralizumab [anti-IL-5R]) and activators of group 2 innate lymphoid cells, the cellular source of considerable type 2 cytokines (eg, tezepelumab [anti-TSLP], etokimab [anti-IL-33], fevipirant, GB001 [anti-CRTH2/DP2]) 3 (Fig 1). Despite having compelling targets and despite their efficacy in other type 2 diseases, these drugs have had varying success in phase 2/3 studies in CRSwNP: benralizumab provided relatively modest reductions of nasal polyp scores and nasal congestion scores, whereas fevipirant and etokimab failed to improve polyp size or symptoms.…”
Section: Type 2 Inflammatory Pathway-targeted Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these drugs were first developed for other type 2 inflammatory diseases (ie, asthma and atopic dermatitis), providing important evidence for safety as well as efficacy against mechanistically similar diseases. Published ongoing trials in CRS include trials of mAbs targeting cytokines or their receptors (lebrikizumab [anti-IL-13], reslizumab [anti-IL-5], benralizumab [anti-IL-5R]) and activators of group 2 innate lymphoid cells, the cellular source of considerable type 2 cytokines (eg, tezepelumab [anti-TSLP], etokimab [anti-IL-33], fevipirant, GB001 [anti-CRTH2/DP2]) 3 (Fig 1). Despite having compelling targets and despite their efficacy in other type 2 diseases, these drugs have had varying success in phase 2/3 studies in CRSwNP: benralizumab provided relatively modest reductions of nasal polyp scores and nasal congestion scores, whereas fevipirant and etokimab failed to improve polyp size or symptoms.…”
Section: Type 2 Inflammatory Pathway-targeted Therapeuticsmentioning
confidence: 99%
“…An inhaled SMD (the DNA enzyme SB010) that targets GATA-3, a molecule controlling the differentiation of group 2 innate lymphoid cells and T H 2 cells, has performed well in patients with allergic asthma, although it has not been studied in CRS. 3 Another promising class of SMDs are those that inhibit the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway and are approved or in the late stage of approval for atopic dermatitis but have not been studied in CRS. 3 Additionally, anticalins are a new class of bioengineered molecules that are based on endogenously occurring lipocalins, have antibody-like specificity, and allow for topical administration.…”
Section: Emerging Areas For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cell–derived alarmins such as IL‐25, IL‐33 and thymic stromal lymphopoietin (TSLP) play a critical role in the pathogenesis of CRS by activating innate immune cells 74 . Biologics targeting IL‐25, IL‐33 and TSLP are potential options for the treatment of severe CRSwNP.…”
Section: T2 Biologics For Asian Crswnp Patients and Patient Selectionmentioning
confidence: 99%
“…Notably, tezepelumab, an anti‐TSLP monoclonal antibody, is currently under phase 3 trial (WAYPOINT) for treating severe CRSwNP, and several Asian centres are engaged in this trial (ClinicalTrials: NCT04851964). Etokimab, an IL‐33 inhibitor, is currently under phase 2 trial for patients with CRSwNP (ClinicalTrials: NCT03614923); however, a recent press release reported that etokimab failed to achieve statistically significant improvement in bilateral NP scores and sinonasal outcome test 22 scores versus placebo at the week 8 time point 74 …”
Section: T2 Biologics For Asian Crswnp Patients and Patient Selectionmentioning
confidence: 99%